Desain Ulang Struktur Bangunan Gedung Hotel Ibis Padang Dengan Tinjauan Fixed Base - Hazmal Herman; Dede Capry; Wiwin Putri Zayu (LPPM Universitas Dharma Andalas, 2022)
Reinforced concrete structure is a structural forming material that is still widely used. Concrete structure has advantages in the ease of materials and also the workmanship. Reinforced concrete is also more effectively used for structures that have a less long span. Ibis Padang Hotel building planning uses reinforced concrete structures with reference to SNI 2847:2013 on Structural Concrete Requirements for Buildings and SNI 1726:2012 on Earthquake Resilience Planning Procedures for Building And Non-Building Structures. The burdens that occurred were reviewed in SNI 1727:2013 on The Indonesian Demolition Regulation for Buildings and Other Buildings. This planning uses a dual system of SRPMK and sliding walls in terms of earthquake anchoring. The concept of this plan is based on the ultimate design that occurs, where the ultimate value must be smaller than the cross-sectional strength of the structural components. Style calculation – style in using the ETABS 2013 program. In addition, there is also a calculation of the Cost Budget Plan. This writing aims to find out the comparison of the structural components of the Ibis Padang Hotel building using Base Isolator with the results of planning using Fixed Base. The beam component comparison obtained a smaller yield of 15.17% for casting volume and 23.64% for repeat weight. The comparison of column components obtained smaller results of 29.17% for casting volume and 24.32% for repeat weight. Comparison of plate components obtained a smaller result of 16.58% for the repeating weight. The comparison of pile cap components obtained a smaller result of 45.98% for casting volume and 2.54% of repeating weight.